IMPACT OF ORGANIZATIONAL CULTURE ON EMPLOYEE’S PERFORMANCE AND JOB SATISFACTION IN HOTEL INDUSTRY (PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: Organisations in hotel industry rely on their workforce for optimum productivity. People contribute  their own special set of values and behaviours to their organization. Establishment with positive organizational culture  has become important, for maintaining a good position in market also it gives satisfaction of its employees so that  organisation achieves its objectives efficiently. Objectives: To explore the impact of organizational culture on employee’s  performance and job satisfaction in hotel industry and to determine the relationship between them. Methodology:  Descriptive research design was adopted. The research was conducted on employees (n=100) working in a 5- star hotel  in Delhi, NCR. A questionnaire was developed consisting of 17 statements pertaining to organizational culture, job  satisfaction and employee performance; Correlation was studied by Karl Pearson’s coefficient of correlation Results: Organizational culture was seen to have positive impact on both, job satisfaction and employee performance (r=0.91  and 0.85) respectively. Job satisfaction and employee performance were also found to be positively correlated (0.87).  Conclusion: Organizational culture is found to be an important element which highly influences job satisfaction and  performance of employees working in hotel industry.
Keywords: Organizational Culture; Job Satisfaction; Employee Performance; Hotel Industry